Fractionation of Xanthium strumarium L. foliage phenolics, in-vitro antioxidant activities, and in-vivo anti-diabetic potential - Asma Shaheen; Sumia Akram; Saima Sharif; Ayoub Rashid; Ahmad Adnan; Muhammad Mushtaq (Frontiers in Chemistry, 2023)
Introduction: The present research aimed to fractionate Xanthium strumarium L. (XSL) foliage phenolics into a set of solvents and evaluate their antioxidant potential and in-vivo anti-diabetic activity against Alloxan monohydrate-induced diabetic mice.Methodology: For this purpose, XSL foliage was fractionated into petroleum ether, ethyl acetate, ethanol, and water via orbital type shaking and tested for the presence of phenolics, and their antioxidant and antidiabetic potential.Results and discussion: The results revealed that the ethyl acetate fraction of XSL foliage contained the highest amount of total phenolics 95.25 mg GAE/g of extract, followed by ethanol (65.14 mg GAE/g), petroleum ether (25.12 mg GAE/g), water (12.20 mg GAE/g), and XSL powder (69.13 mg GAE/g). At the end of treatment time (day 18 of oral administration of 400 mg/kg body weight of mice), the ethyl acetate fraction significantly (p ≤ 0.05) lowered blood glucose level (353 ± 10.6 to 220 ± 25.5 mg/dL) which might due to the elevated level of phenolic compounds in this fraction.Conclusion: Overall, it can be speculated that ethyl acetate and ethanol may work efficiently for the enrichment of XSL phenolic without compromising their antidiabetic potential.